2021
DOI: 10.3390/cells10102730
|View full text |Cite
|
Sign up to set email alerts
|

Activation of mTORC1 by Free Fatty Acids Suppresses LAMP2 and Autophagy Function via ER Stress in Alcohol-Related Liver Disease

Abstract: Alcohol-related liver disease (ALD) is characterized by accumulation of hepatic free fatty acids (FFAs) and liver injury. The present study aimed to investigate if mechanistic target of rapamycin complex 1 (mTORC1) plays a role in FFA-induced organelle dysfunction, thereby contributing to the development of ALD. Cell studies were conducted to define the causal role and underlying mechanism of FFA-activated mTORC1 signaling in hepatocellular cell injury. C57BL/6J wild-type mice were subjected to chronic alcohol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…We observed that lysotracker staining and thus lysosomal activity in PA-treated embryos was significantly lowered, indicating that autophagosome degradation was disrupted. This interruption in lysosomal activity is not limited to preimplantation embryos, as PA treatment also significantly lowered the hydrolase activity of lysosomes in INS1 β-cells ( 50 ) as well as lowered LAMP2 levels in mouse hepatocytes ( 48 ). On the other hand, the addition of OA in PA treatment restored normal levels of autophagosome formation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We observed that lysotracker staining and thus lysosomal activity in PA-treated embryos was significantly lowered, indicating that autophagosome degradation was disrupted. This interruption in lysosomal activity is not limited to preimplantation embryos, as PA treatment also significantly lowered the hydrolase activity of lysosomes in INS1 β-cells ( 50 ) as well as lowered LAMP2 levels in mouse hepatocytes ( 48 ). On the other hand, the addition of OA in PA treatment restored normal levels of autophagosome formation.…”
Section: Discussionmentioning
confidence: 94%
“…Exposure of HepG2 cells to PA revealed that autophagy is induced by the protein kinase C (PKC) pathway as the high level of DAG presence from PA exposure elevated PKC-α activation ( 47 ). Another study of mouse hepatocytes suggested that autophagy was dependent on the mammalian target of rapamycin (mTOR) pathway, where PA exposure elevated ER stress and reduced lysosomal-associated membrane protein 2 (LAMP2) expression, thus impairing the autophagic mechanisms ( 48 ). Further investigation is required to determine if either PKC or mTOR pathway is implicated in mediating PA treatment effects on mouse preimplantation embryos.…”
Section: Discussionmentioning
confidence: 99%
“…When cells are transfected with GFP-RFP-LC3, yellow puncta indicate autophagosome and red puncta indicate autolysosome [ 25 ]. GFP is sensitive to acidic PH in the lysosome and GFP fluorescence signals is quenched in the autolysosome [ 26 , 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that repression of mTORC1 by hayatine, an mTORC1 inhibitor, can enhance autophagy flux in tumor cells [39]. Other studies have shown that activation of mTORC1 by palmitic acid (PA) impaired autophagy flux and repressed lysosomal associated membrane protein-2 (LAMP2) expression in mouse Hepa-1c1c7 cells [40]. Furthermore, mTORC1 inhibition by rapamycin showed an induction of autophagy in C57BL/6J mice fed with an alcohol-containing diet for 8 weeks [40].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown that activation of mTORC1 by palmitic acid (PA) impaired autophagy flux and repressed lysosomal associated membrane protein-2 (LAMP2) expression in mouse Hepa-1c1c7 cells [40]. Furthermore, mTORC1 inhibition by rapamycin showed an induction of autophagy in C57BL/6J mice fed with an alcohol-containing diet for 8 weeks [40]. mTORC1 hyperactivation was reported in the isolated islet of type 2 diabetes patients and type 2 diabetes animal models [41].…”
Section: Introductionmentioning
confidence: 99%